PĒTERA EVAŅĢĒLIJS UN KUNGS: VAI KRISTUS TIKAI ŠķIETAMI BIJA CILVĒKS?: The Gospel of Peter: Was Christ Really a Human? - Balode, Dace (Cel̜š, 2013)
The article focuses on Christology represented in the Gospel of Peter. After showing some facts about the discovery of the manuscript of the gospel, it draws the attention to early evidence of Peter's gospel in the texts of the Church Fathers, where the tendency is to see, that the Gospel of Peter was regarded as docetic. Unfortunately, they do not give to a modern reader a direct reference to the Gospel of Peter, where this belief could be proven. However, the use of the Gospel of Peter in church in early times shows that not everyone has believed the gospel is heretical. Also the text, which is available from the Gospel of Peter does not allow definitely conclude that the author represented docetic Christology. The body of Christ is called the Lord, so that the divine is identified with flesh. In addition, the emphasis is laid on the resurrection of Christ, about what the gospel offers a unique story, namely, the story of the process of resurrection. The article offers the Latvian translation of this dramatic scene. It is concluded that the most likely Peter's gospel does not represent docetic Christology. The parallels of apocalyptic literature may allow a better understanding of the gospel.